E-COMMERCE IN SUPPLY CHAIN MANAGEMENT: ITS INTRODUCTION AND PROSPECTS IN THE LIGHT INDUSTRY - N.Kashurnikov, Sergey; V.Sevalnev, Viacheslav; V.Truntsevsky, Yuri; V.Cherepanova, Ekaterina; G.Berestneva, Olga (International Journal of Supply Chain Management, 2019)
The research deals with current trends of e-commerce in supply chain management through the example of light industry. It is shown that one of the current trends in supply chain management is human labor reduction and almost complete automation of warehouse and transport operations. The practice of domestic online stores in e-commerce is regarded. It has been revealed that for domestic stores there is a lag in using innovative means. This is explained by the small volume of sales. The introduction of innovations, which include business analytics, mobile technologies and applications, omni channel logistics, the use of electric vehicles, autonomous vehicles and drones, the use of cloud computing technologies, e-commerce, automatic identification and data collection, 3D printing, has not become popular in domestic online stores.